2018
DOI: 10.1002/mus.26058
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal excitability changes in normal human aging

Abstract: The results are consistent with progressive depolarization of the resting sarcolemmal potential with normal aging. This may be an important mechanism in explaining age-related muscle decline. Muscle Nerve 57: 981-988, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…MVRC recordings were made from the distal 25% of RF and near the distal palpated end of TA to avoid the motor points. Recordings of both muscles were performed in series within 2 hours in each subject, as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MVRC recordings were made from the distal 25% of RF and near the distal palpated end of TA to avoid the motor points. Recordings of both muscles were performed in series within 2 hours in each subject, as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The electrophysiological technique of multifiber muscle velocity cycle recording (MVRC), as described in previous work, is a reliable and repeatable technique that has been used to examine sarcolemmal excitability properties in physiological and disease states in vivo . No significant differences in MVRC parameters have been described in the limited studies comparing normal human muscles using this technique .…”
Section: Introductionmentioning
confidence: 99%
“…Recordings of both muscles were performed in series within 2 hours in each subject, as described elsewhere. 5 In a small subset of the cohort (n = 5), MVRC recordings at rest were attempted in the soleus in addition to TA and RF within the same recording session. Soleus was identified by palpation and identification of the Achilles tendon and the gastrocnemius, with recordings performed medial to the Achilles tendon but distal to the end of the medial gastrocnemius.…”
Section: Study Protocolmentioning
confidence: 99%
“…The electrophysiological technique of multifiber muscle velocity cycle recording (MVRC), as described in previous work, 3 is a reliable and repeatable technique 4 that has been used to examine sarcolemmal excitability properties in physiological 3,5 and disease states in vivo. 6,7 No significant differences in MVRC parameters have been described in the limited studies comparing normal human muscles using this technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, Z'Graggen and Bostock later found that multi-fiber recordings, obtained by direct stimulation and recording from the same bundle of muscle fibers, provide a fast and simple method of obtaining such recordings in vivo 7 . A sequence of paired pulse electrical stimuli with varying interstimulus intervals (ISIs) is used in this method 7,8,9,10,11 .…”
Section: Introductionmentioning
confidence: 99%